The Serine/Threonine-Protein Phosphatase 1 From Haemonchus contortus Is Actively Involved in Suppressive Regulatory Roles on Immune Functions of Goat Peripheral Blood Mononuclear Cells - Ehsan, Muhammad; Wang, WenJuan; Gadahi, Javaid Ali; Hasan, Muhammad Waqqas; Lu, MingMin; Wang, YuJian; Liu, XinChao; Haseeb, Muhammad; Yan, RuoFeng; Xu, LiXin; Song, XiaoKai; Li, XiangRui (Frontiers in Immunology, 2018)
Serine/threonine-protein phosphatases (STPs), as integral constituents of parasitic excretory/secretory proteins, are assumed to be released during the host–parasite interactions. However, knowledge about these phosphatases and their immunoregulatory and immune protective efficiencies with host peripheral blood mononuclear cells (PBMCs) is scant. In this study, an open reading frame of STP from Haemonchus contortus designated as HcSTP-1 was amplified and cloned using reverse-transcription-polymerase chain reaction (RT-PCR) method. The 951-bp nucleotides sequence was encoded to a protein of 316 amino acid residues, conserved in characteristics motifs GDXHG, GDYVDRG, GNHE, HGG, RG, and H. The HcSTP-1 protein was detected at approximately 35 kDa as recombinant protein fused in an expression vector system and resolved on sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Immunohistochemically, HcSTP-1 was found to be localized in both male and female adult worm sections. Using immunofluorescence assay, the binding activity of rHcSTP-1 was confirmed on surface of goat PBMCs, which resulted in expression of multiple cytokines and various immunoregulatory activities in vitro. The RT-PCR results showed that mRNA level of interleukin-2, TGF-β1, IFN-γ, and IL-17 (with 10 µg/ml) was upregulated and IL-10 was decreased. However, IL-6 showed no change after PBMCs incubated with rHcSTP-1 protein. Further functional analysis showed that migratory activity of cells, intracellular nitrite production (NO), and apoptotic efficiency of PBMCs were elevated at significant level, whereas the proliferation of goat PBMCs and monocytes-associated major histocompatibility complex (MHC)-I and MHC-II expressions were decreased significantly at concentration-dependent fashion. Our results showed that the HcSTP-1 protein engaged in vital suppressive regulatory roles on host immune cells, which might represent a potential molecular target for controlling H. contortus infection in future.